The mechanism regulating the cytotoxicity of γδ T cells activated by mycobacterium tuberculosis heat-resistant antigen based on RNA-seq analysis - Song, Yamin; Guo, Fangzheng; Dai, Huiting; Zhou, Xiaoyu; Dong, Sihang; Zhang, Hui; Qian, Zhongqing; Li, Baiqing; Wang, Xiaojing; Xu, Tao; Wang, Hongtao (Frontiers in Immunology, 2026)
IntroductionTuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a major global health threat. γδ T cells, critical innate immune responders, provide rapid anti-TB defenses and act as a bridge between innate and adaptive immunity. Studies have demonstrated that γδ T-cell activation by phosphoantigens is mediated by butyrophilin subfamily 3 member A1 (BTN3A1), leading to enhanced cytokine production and cytotoxicity. Mtb heat-resistant antigen (Mtb-HAg), extracted from Mtb H37Ra, specifically activates γδ T cells and induces cytokine secretion. However, the contribution of Mtb-HAg to γδ T cell-mediated cytotoxicity and its dependence on BTN3A1 remain unclear.MethodsThis study explored the regulatory mechanism of Mtb-HAg on the cytotoxic function of γδ T cells through RNA-Seq analysis and functional validation methods. The RNA-Seq analysis to profile the transcriptome of Mtb-HAg-activated γδ T cells.The expression of key cytotoxic factors was analyzed using ELISA, and the capacity of activated γδ T cells to inhibit intracellular Mtb growth was assessed using a co-culture assay with Mtb-infected macrophages. The specific role of BTN3A1 was investigated using a blocking antibody to assess its impact on activation markers, cytotoxic factor secretion, and mycobacterial killing efficiency.ResultsRNA-Seq analysis revealed that Mtb-HAg-activated γδ T cells are significantly enriched for genes associated with cytotoxic immune responses, with significant upregulation of key cytotoxic factors granzyme B (GzmB) and perforin (PFP), indicating that the cytotoxic function of these cells was activated at the transcriptional level. Subsequently, protein expression analysis revealed that the secretion of GzmB and PFP was increased in Mtb-HAg-activated γδ T cells. Meanwhile, intracellular Mtb growth inhibition assays demonstrated that activated γδ T cells lysed infected target cells and suppressed intracellular Mtb proliferation. We further found that BTN3A1 blockade significantly reduced the expression of CD69 and CD107a in γδ T cells, decreased the secretion of GzmB and PFP, and diminished the killing efficiency of γδ T cells against Mtb-infected macrophages.ConclusionOur findings demonstrated that Mtb-HAg enhances the cytolytic activity of γδ T cells and inhibits intracellular Mtb growth, with BTN3A1 playing a regulatory role in these processes.